2020
DOI: 10.1002/we.2600
|View full text |Cite
|
Sign up to set email alerts
|

Development of fragility curves of land‐based wind turbines with tuned mass dampers under cyclone and seismic loading

Abstract: Passive damping systems have been widely studied to improve the response of wind turbine structures under operational conditions. However, there is insufficient information on how these systems enhance reliability for extreme loads. Wind farm construction has been growing rapidly in recent decades, thereby moving wind turbine structures to sites with higher seismic and hurricane hazards. This research presents a numerical study performed on three land‐based wind turbines, similar to typical turbines installed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…48 Nevertheless, for simplicity, OWT is often considered as an overall lightly damped structure. Various damping ratios were adopted in recent studies, ranging from 1%, 9,42,[49][50][51] to 2%, 16,52 or 3% 7,10 of critical damping. There were also a few examples where the potential effect of aerodynamic damping was directly accounted for using the Rayleigh damping assumption, leading to high overall damping ratios such as 7.5%, 53 10%, 18 or even 12%.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…48 Nevertheless, for simplicity, OWT is often considered as an overall lightly damped structure. Various damping ratios were adopted in recent studies, ranging from 1%, 9,42,[49][50][51] to 2%, 16,52 or 3% 7,10 of critical damping. There were also a few examples where the potential effect of aerodynamic damping was directly accounted for using the Rayleigh damping assumption, leading to high overall damping ratios such as 7.5%, 53 10%, 18 or even 12%.…”
Section: 12mentioning
confidence: 99%
“…The widely-used structure-specific S a (T 1 ) (such as in 7,10,20,33,34 ) was proven to have good efficiency. On the other hand, acceleration-related IMs, including the commonly used PGA (such as in 21,35,49 ), were found to have poor efficiency and proficiency. For wind, all four wind IMs were found to have poor efficiency, practicality and proficiency.…”
Section: Recommended Intensity Measures For Owt Multi-hazard Fragilit...mentioning
confidence: 99%
“…However, the anti‐TC optimal control scheme of nEWSP has not been deeply studied on the wind field characteristics and its influence. The main difficulty is that in the face of complex and changeable working conditions such as strong winds, severe turbulence, and sudden changes in wind direction during TCs, the wind turbine needs to frequently perform various control actions such as speed limit [18], pitch change [19], yaw [15] and passive damping systems [20], to clarify the change law of wind turbine structural loads under complex environmental conditions, is an important basis for designing safe operation control schemes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the impact of tropical cyclone damage on onshore wind turbines from an engineering perspective. Martín del Campo et al Martín del Campo et al (2021) found that modifying the structure of onshore turbines by adding passive damping systems would reduce turbine fragility by 80%. Jaimes et al Jaimes et al (2020) employ a probabilistic risk assessment to explore the economic impact of tropical cyclones on onshore wind farms in Mexico.…”
Section: Introductionmentioning
confidence: 99%